ΑΡΧΕΙΑΚΕΣ ΠΗΓΕΣ ΓΙΑ ΤΗΝ ΙΣΤΟΡΙΑ ΤΗΣ ΚΟΙΝΟΤΗΤΑΣ ΤΗΣ ΑΓΙΑΣ ΤΡΙΑΔΑΣ ΤΗΣ ΒΙΕΝΝΗΣ. ΝΕΕΣ ΠΡΟΟΠΤΙΚΕΣ - ΣΤΑΣΙΝΟΠΟΥΛΟΥ ΜΑΡΙΑ (Eoa kai Esperia, 2007)
The aim of this paper is to present recent efforts to classify the archivalmaterials of the Greek-Orthodox community of the "Holy Trinity" founded inthe 18th century in Vienna. Archival material concerning the community hasbeen rarely published and extremely few historians in the past century weregiven the chance to use the files kept in the building still housing today thechurch, the offices of the community, the school and the Greek-OrthodoxMetropolis of Austria. The chair of Modern Greek Studies at the Department of Byzantine andModern Greek Studies of the University of Vienna was invited by theMetropolis of Austria and the "Holy Trinity" community council in 2005 toclassify the archival materials. The project has been carried out under mysupervision with the financial support of the Greek Ministry of Culture and incollaboration with the Institute for Research of Church Archival Sources(Austria). The protocol books of the community were digitalized in 2006, while thefiles were cleaned, put in secure acid free boxes and classified during 2007. Aprovisional catalog in database format (Augias) and a print-out now exist andcan be consulted at the Department of Byzantine and Modern Greek Studies.Further steps will hopefully include a presentation of the new archive,publication of the catalog and regular accessibility for research purposes, aworkshop and a series, which will include publications based on research in thearchive.